2000
DOI: 10.1002/(sici)1097-0290(20000620)68:6<689::aid-bit13>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting viral cell-targeting abilities in a single polypeptide, non-infectious, recombinant vehicle for integrin-mediated DNA delivery and gene expression

Abstract: A recombinant, multifunctional protein has been designed for optimized, cell‐targeted DNA delivery and gene expression in mammalian cells. This hybrid construct comprises a viral peptide ligand for integrin αVβ3 binding, a DNA‐condensing poly‐L‐lysine domain, and a complete, functional β‐galactosidase protein that serves simultaneously as purification tag and DNA‐shielding agent. This recombinant protein is stable; it has been produced successfully in Escherichia coli and can be purified in a single step by af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The transgene expression levels and stability that were reached in this study were comparable or higher than those observed with previous prototypes of artificial viruses based on multifunctional proteins [15,53,54,56,57], The less active modular protein version, namely the construct HKRN, achieved approximately 18% of the expression level observed when using lipofectamine ( Figure 2C). The slight differences in the ability to retain and deliver expressible DNA are obviously due to the alternative disposition of functional motifs, and the end terminal location of the cationic K10 peptide seems to be especially convenient for the performance of the whole vehicle.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The transgene expression levels and stability that were reached in this study were comparable or higher than those observed with previous prototypes of artificial viruses based on multifunctional proteins [15,53,54,56,57], The less active modular protein version, namely the construct HKRN, achieved approximately 18% of the expression level observed when using lipofectamine ( Figure 2C). The slight differences in the ability to retain and deliver expressible DNA are obviously due to the alternative disposition of functional motifs, and the end terminal location of the cationic K10 peptide seems to be especially convenient for the performance of the whole vehicle.…”
Section: Discussionsupporting
confidence: 79%
“…From the material science point of view, the organization of protein-based cages has been classified according to rather general schemes [9,52], but the precise architecture of proteinaceous artificial viruses other than those based on VLPs remains poorly explored. In fact, multifunctional proteins based on large scaffold proteins such as E. coli b-galactosidase for instance [53,54], organize as amorphous polydisperse protein clusters whose properties seem to be defined by protein features (the enzyme is a tetramer of approximately 460 kDa [55]), rather than by the presence of DNA [56]. Upon addition, plasmid DNA does not modify the morphology of the complexes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of oligolysine ELP block copolymers could be difficult due to the repetitive amino acid block often flagged as deleterious by host organisms; moreover, oligo-lysine ELP may also pose a cytotoxic effect due to the high cationic charge, thereby destabilizing anionic membranes of organelles and/or cells. Yet despite these hurdles, success with lysine repeats is reported in the literature where fusion proteins containing oligo-lysines were successfully expressed in prokaryotic expression systems for gene transfer applications (32,33). Another interesting study was reported by Kiick et al (44), which reported the incorporation of non-natural amino acids into biosynthetic polypeptides, further diversifying the application of polypeptides as functional materials.…”
Section: Discussionmentioning
confidence: 99%
“…The inherent characteristics of these biomaterials allow the study of desired properties for successful biosynthetic gene delivery vectors via a structure-function relationship difficult to achieve by synthetic polymers and hence the impetus for IBN platforms. Arís et al (32) reported the first stable oligolysine encoding fusion protein, b-galactosidase, prepared by DNA cloning technology for gene delivery. The fusion protein consists of an N-terminal oligolysine domain for DNA condensation and an arginine-glycine-aspartic acid (RGD) sequence inserted on a solvent exposing loop of the protein for integrin targeting.…”
Section: Introductionmentioning
confidence: 99%
“…The same effect was observed at the level of luciferase transgene expression, indicating that the DNA/Gal-pOrn vector was not only able to adhere and enter preferentially into hepatocytes, but it could also transfect them. Many different domains of known proteins and sugars have been used for cell targeting of modular vectors, like galactose (Wu and Wu 1987), transferrin (Wagner et al 1990), foot-andmouth disease virus integrin interacting peptide (Aris et al 2000;Aris and Villaverde 2003;Domingo-Espín et al 2011), nerve growth factor Zeng et al 2004), surfactant protein A (Ross et al 1995), rabies virus glycoprotein (Kumar et al 2007), tetanus toxin fragment Hc (Box et al 2003;Knight et al 1999), cholera toxin b chain (Barrett et al 2004), and neurotensin (Navarro-Quiroga et al 2002). In an interesting study, Arango-Rodríguez and colleagues showed that they could target only substantia nigra neurotensin high affinity receptor positive neurons by means of a modular vector that displayed neurotensin, while no other neurons were transfected (Arango-Rodriguez et al 2006).…”
Section: Cell Attachment and Cell Targetingmentioning
confidence: 99%